Effects of variable injection rate on reservoir responses and implications for CO2 storage in saline aquifers. Issue 4 (13th May 2019) - Li, Cai; Maggi, Federico; Zhang, Keni; Guo, Chaobin; Gan, Yixiang; El‐Zein, Abbas; Pan, Zhejun; Shen, Luming
Abstract: Past reservoir simulations of carbon dioxide (CO2 ) storage in saline aquifers have shown that the injection procedure can influence CO2 storage efficiency and injectivity. To investigate the influence of injection rate and timing on reservoir dynamics and storage performance, scenarios of continuous and intermittent injections were devised for storing 1 million tonnes of CO2 per year for 30 years and were assessed through numerical simulations on saline aquifers constructed with real field data. Our results show that almost all the intermittent injections need higher injection pressure than the constant injection for the same targeted amount of CO2 . Only one intermittent injection showed the potential to have a lower injection pressure than the constant injection. The injectivity for the constant injection consistently declines over the years, while the intermittent injections result in an injectivity above a reference value for some years, with the number of years that maintain the injectivity linearly increasing with the length of the injection break. The injectivity for an intermittent injection peaks a few years later after the injection starts. Intermittent injections improve the residual and solubility trapping by up to 15% only in the first few years of injection, but the differences in trapping efficiencies among all the injections are within a few percent in the long term. Therefore, the intermittent injections would be useful for a CO2 storage project to make the best use of a reservoir in 5–10 years under the injection pressure restrictions. © 2019 Society of Chemical Industry and John Wiley & Sons, Ltd.